(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
This article contains, in the first place, a reflection on the link established between the mother’s tongue –in its qualitative experiential variety and historical determinations– and the phenomenon of existential madness and grief, particularly with the distorted guiding of an “unidentified” emotionality, eluded or denied, towards speech acts. In the second place, the relationship between the mother’s tongue and different types of existential madness, in the context of community-family fragmentation experiences and sequels of exiles and diasporas of the twentieth century, is observed. In the third place, the autobiographical and critical experience of ethnographic and testimonial writing of the language is examined. Finally, this article aims to establish a phenomenological view of an ‘oral madness’, conditioned by sequels of historical extermination. It is not easy to notice, at first glance, the ambiguous nexus of plural subjects with the mother’s tongue, its reflection in the collective psyche as a concealed form of madness, monomania, alienation and fragmented subjectivity. Likewise, the impact of this particularity on communicative action and gregarious linguistic coexistence is neither easily noticed.